Validation of an evaluation instrument for responders in tactical casualty care simulations - Maria Del Carmen Usero-Pérez; Maria Lourdes Jiménez-Rodríguez; Alexandra González-Aguña; Valentín González-Alonso; Luis Orbañanos-Peiro; Jose María Santamaría-García; Jorge Luís Gómez-González (Universidade de São Paulo, 2020)
Objective: to construct and validate a tool for the evaluation of responders in tactical casualty care simulations. Method: three rubrics for the application of a tourniquet, an emergency bandage and haemostatic agents recommended by the Hartford Consensus were developed and validated. Validity and reliability were studied. Validation was performed by 4 experts in the field and 36 nursing participants who were selected through convenience sampling. Three rubrics with 8 items were evaluated (except for the application of an emergency bandage, for which 7 items were evaluated). Each simulation was evaluated by 3 experts. Results: an excellent score was obtained for the correlation index for the 3 simulations and 2 levels that were evaluated (competent and expert). The mean score for the application of a tourniquet was 0.897, the mean score for the application of an emergency bandage was 0.982, and the mean score for the application of topical haemostats was 0.805. Conclusion: this instrument for the evaluation of nurses in tactical casualty care simulations is considered useful, valid and reliable for training in a prehospital setting for both professionals who lack experience in tactical casualty care and those who are considered to be experts.